2023
DOI: 10.3389/fsufs.2023.1163507
|View full text |Cite
|
Sign up to set email alerts
|

High occurrence of hepatitis E virus in raw pork liver and pork liver pâté produced in the Canadian province of Quebec

Abstract: The Hepatitis E virus is widespread throughout the world and causes sporadic cases of liver disease. In industrialized countries, its transmission is zoonotic, with pigs, deer, and wild boar being major reservoirs. Humans can be infected by ingesting raw or undercooked contaminated meat products. In the Canadian province of Quebec, HEV has been detected previously in pork liver and chops. In the present study, we analyzed 83 pork liver pâtés sold in local grocery stores and 79 raw pork livers obtained from Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For example, the majority of infections in France belong to clades e, f, and g [ 34 ] and infections in Italy are mostly associated with subtypes 3f [ 16 ]. The Canadian pork isolates mostly belong to subtypes 3a and 3b [ 22 , 23 ]; therefore, the presence of a few clinical isolates in Canada that belong to subtypes 3c, 3e, 3f, and 3g could be attributed to the consumption of imported meat products, or possibly travel to endemic regions of Europe. An extensive phylogenetic analysis of HEV-3 isolated from farmed pigs in Europe has also revealed that subtypes 3c, 3e, 3f, and 3g are most common, while there are only a few isolates that belong to 3a, and 3b [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the majority of infections in France belong to clades e, f, and g [ 34 ] and infections in Italy are mostly associated with subtypes 3f [ 16 ]. The Canadian pork isolates mostly belong to subtypes 3a and 3b [ 22 , 23 ]; therefore, the presence of a few clinical isolates in Canada that belong to subtypes 3c, 3e, 3f, and 3g could be attributed to the consumption of imported meat products, or possibly travel to endemic regions of Europe. An extensive phylogenetic analysis of HEV-3 isolated from farmed pigs in Europe has also revealed that subtypes 3c, 3e, 3f, and 3g are most common, while there are only a few isolates that belong to 3a, and 3b [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Canada, HEV-3 infections in clinical cases and their molecular characteristics have not been described. However, several studies have reported the presence of HEV-3 genome in swine and cervid species as well as pork products [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%